The analgesic potential of curcumin patch on post-operative orofacial pain - A/Prof Tantry Maulina; Dr Yohanes Yoppy Purnomo; Dr Nadya Khamila; Dr, PhD Devy Firena Garna; A/Prof Arief Cahyanto; A/Prof Endang Sjamsudin (Elsevier, 2023)
Aim or Purpose: Despite of its well-acknowledged analgesic potential, curcumin's low bioavailability has also been recognized. Piperine, a substance naturally contained in pepper, has been known for its effect on increasing curcumin bioavailability. The aim of this study was to investigate the analgesic potential of curcumin and the addition of piperine as an adjuvant therapy in the management of acute postoperative orofacial pain. Materials and Methods: This pragmatic trial recruited 75 patients that underwent oromaxillofacial surgery at Unpad Dental Hospital, Bandung, Indonesia. Participants were randomly assigned to three groups: the group that did not receive any intervention other than the post-operative standard treatment (POST), the second group that received POST and non-piperine curcumin patch, and the third group that received POST and piperine-combined curcumin patch. Participants' pain intensity was evaluated by the face, leg, activity, cry, and consolability (FLACC) pain scale and measuring the salivary prostaglandin-E2 (PGE2) level at two-time points. All data were gathered and analyzed to compare the within and between-group results. Results: Within groups comparison of the FLACC scores for two evaluation points showed significant differences for all groups (p < 0.01). For salivary PGE2 analysis, a comparison of the non-piperine group to the piperine group also showed significant results. Conclusions: Even though curcumin showed its potent analgesic effect, the addition of piperine to the curcumin patch in the current study did not provide the significant effect as expected. Further investigation is therefore, of importance.